Pharmacological Activities of Bunga lawang (Illicium verum) - Endang Kusuma Intan; Ani Florida Ngete; Riskatul Jannah; Teguh Setiawan Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Star anise (Illicium verum) has long been used in traditional medicine and the food industry to prevent cold and relieve pain. The traditional use of star anise (Illicium verum) is evidenced from South Asia and West Asia, where the star anise has been consumed for the treatment of a number of disease disorders. In this article, the discussion on star anise (Illicium verum) is focused on its chemical composition and medical value, especially on its pharmacological activities such as antimicrobial, antioxidant, anti-insect, anticancer, anti-inflammatory, antidiarrheal, antifungal and the use of star anise as orthodox medicine and traditional applications.